Development of PowerPoint-iSpring Learning Media Integrated Prompting Questions on Chemical Equilibrium for Class XI SMA/MA - Amelia Difa; Guspatni Guspatni (Universitas Negeri Padang, 2022)
Chemistry is a tricky subject because it is abstract and complex so, students have difficulty learning. Understanding it can be explained by three levels of chemical representation, namely macroscopic-, submicroscopic and symbolic. Learning media help teachers convey material quickly and make the material good because it contains exciting features. One of them is PowerPoint-iSpring which has a question feature. Prompting questions involve students more actively because they direct students to form thinking processes. Chemical equilibrium is a complex subject to understand. The study aims to develop an integrated PowerPoint-iSpring instructional media for prompting in class XI SMA/MA and determine the level of validity of the media developed using the Plomp model. The research subjects were SMAN 7 Padang teachers, UNP chemistry lecturers, and UNP IT lecturers as content validators, constructors, and media experts. The object of this research is thelearning media for PowerPoint-iSpring integrated prompting questions. The research instrument was a validation questionnaire and an interview sheet. This research was only carried out until prototype 3 due to time constraints. The results of the analysis of the validity test in stage I obtained the Aiken's V value < 0.8 invalid category in content analysis, constructs, and Aiken’s V value < 0,92 invalid category in media expert assessments so that stage II validation was carried out where all components obtained the results of Aiken's V value > 0.8 valid category in content analysis, construct, and Aiken’s V value > 0,92 valid category in media expert. Keywords : PowerPoint-iSpring, Learning Media, Prompting Questions, Chemical Equilibrium. Kimia merupakan mata pelajaran yang sukar karena bersifat abstrak dan kompleks sehingga siswa mengalami kesulitan dalam belajar. Kimia bisa dipahami dengan tiga level representasi kimia yaitu makroskopik-, submikroskopik dan simbolik. Media pembelajaran membantu guru menyampaikan materi dengan mudah serta membuat materi menjadi bagus karena memuat fitur yang menarik. salah satunya PowerPoint-iSpring yang memiliki fitur pertanyaan. Pertanyaan prompting melibatkan siswa lebih aktif karena mengarahkan siswa agar terbentuk proses berpikir. Kesetimbangan kimia merupakan materi yang sulit dipahami. Penelitian bertujuan untuk mengembangkan media pembelajaran PowerPoint-iSpring terintegrasi prompting pada materi kelas XI SMA/MA dan menentukan tingkat validitas media yang dikembangkan dengan menggunakan model Plomp. Subjek penelitian adalah guru SMAN 7 Padang, dosen kimia UNP, serta dosen IT UNP selaku validator konten, konstruk, dan ahli media. Objek penelitian ini adalah media pembelajaran PowerPoint-iSpring terintegrasi pertanyaan prompting. Instrumen penelitian ini adalah angket validasi dan lembar wawancara Penelitian ini yang hanya dilaksanakan hanya sampai prototipe 3 dikarenakan keterbatas Keywords : PowerPoint-iSpring, Learning Media, Prompting Questions, Chemical Equilibrium.